PENGARUH HARGA DAN KUALITAS TERHADAP KEPUASAN KONSUMEN AIR MINUM KEMASAN MEREK WAITA PADA CV. PANGKY KABUPATEN MAMUJU - Quraisy, Hasbullah (Forecasting : Jurnal Ilmiah Ilmu Manajemen, 2019)
Consumer satisfaction is one thing that is very important for the sustainability of a business. The purpose of this study was to determine the effect of price and quality on consumer satisfaction of Waita brand bottled water on CV. Pangky Mamuju Regency. This type of research is quantitative with the number of respondents as much as 60. The method of data analysis uses multiple linear regression with F test and t test in testing the research hypothesis. The results showed that partially and simultaneously the price and quality variables had a positive and significant effect on consumer satisfaction.